واقع العملية التعليمية عن بعد من وجهة نظر طلبة معهد التربية البدنية والرياضية في ظل جائحة كورونا - لغواطي, حمزة ((Institut d’Éducation Physique et Sportive/Université de Mostaganem), 2021)
ملخص البحث: يهدف هدا البحث إلى دراسة العملية التعليمية عن بعد في ظل جائحة كورونا من وجهة نظر الطلبة بمعهد التربية البدنية و الرياضية بولاية مستغانم، و تبلورت إشكالية البحث انطلاقا من اهتمام كافة المؤسسات التعليمية بتطبيق التعليم عن بعد في ظل الظروف المزرية التي مر بها العالم لجائحة كورونا، اد سعى الطالب الباحث للإجابة على الأسئلة التالية: 1. ما واقع العملية التعليمية عن بعد من وجهة نظر طلبة معهد التربية البدنية والرياضية بمستغانم؟ 2. ما مدى مشاركة وتفاعل طلبة معهد التربية البدنية والرياضية بمستغانم في العملية التعليمية عن بعد؟ 3. ما مدى استيعاب وفهم طلبة معهد التربية البدنية والرياضية بمستغانم للمادة العلمية عن بعد للمحتوى الالكتروني؟ ولتحقيق هدا الغرض تم اقتراح الفرضيات التالية: 1. إن واقع العملية التعليمية عن بعد لا يسمح بالسير الحسن للدروس من وجهة نظرطلبة معهد التربية البدنية والرياضية. 2. طلبة معهد التربية البدنية والرياضية يواجهون صعوبة في المشاركة والتفاعل مع العملية التعليمية حسب وجهة نظرهم. 3. لا يؤثر المحتوى الالكتروني في قدرة فهم واستيعاب الطلبة بمعهد التربية البدنية والرياضية. 4. تم إتباع المنهج الوصفي واستخدمت استبانة خاصة بأغراض البحث اشتملت على 31 فقرة توزعت على 3 محاور وهي واقع العملية التعليمية عن بعد، تفاعل و مشاركة الطلبة في العملية التعليمية عن بعد، المحتوى الالكتروني، وتم تطبيقها على عينة اختيرت بطريقة عشوائية عددها 107طالبا من معهد التربية البدنية و الرياضية،وخلص البحث إلى مجموعة من النتائج كان أهمها أن واقع العملية التعليمية عن بعد لا يسمح بالسير الحسن للدروس من وجهة نظرطلبة معهد التربية البدنية والرياضية. الكلمات المفتاحية :العملية التعليمية، التعليم عن بعد . Study summary:This research aims to study the distance educational process in light of the Corona pandemic from the point of view of the students at the Institute of Physical Education and Sports in the state of Mostaganem, and the problem of the research crystallized from the interest of all educational institutions in applying distance education in light of the miserable conditions that the world went through due to the Corona pandemic, The researcher sought to answer the following questions 1. What is the reality of the distance learning process from the point of view of the students of the Institute of Physical Education and Sports in Mostaganem? 2. What is the extent of participation and interaction of students of the Institute of Physical Education and Sports in Mostaganem in the distance learning process? 3. What is the extent to which the students of the Institute of Physical Education and Sports in Mostaganem comprehend and understand the distance scientific subject of the electronic content? To achieve this purpose, the following hypotheses were proposed: 1. The reality of the distance learning process does not allow the good conduct of lessons from the point of view of the students of the Institute of Physical Education and Sports. 2. Students of the Institute of Physical Education and Sports face difficulty in participating and interacting with the educational process according to their point of view. 3. The electronic content does not affect the students' ability to understand and comprehend at the Institute of Physical Education and Sports. The descriptive approach was followed and a special questionnaire was used for the purposes of the research, which included 31 paragraphs distributed on 3 axes, which are the reality of the distance educational process, the interaction and participation of students in the distance educational process, electronic content, and it was applied to a randomly selected sample of 107 students from the Institute of Physical Education and mathematical, and the research concluded that the degree of impact of the distance learning process is ineffective from the students' point of view :key words: The educational process, distance education
MEPS-2021-27
Keywords: العملية التعليمية - التعليم عن بعد / The educational process - distance education